Redescription of Austrosimulium bancrofti (Taylor) (Diptera: Simuliidae): Australia’s second-worst problem black fly - Craig, Douglas A. (Zootaxa, 2019)
Though the taxonomic establishment of Austrosimulium bancrofti (Taylor) was muddled, the species, because of its pest status, has been the most highly researched black fly in Australia. The literature is, however, widely spread. This current work consolidates much of that and provides redescription of all stages.